ChemInform Abstract: Chemoselective Addition of Halomethyllithiums to Functionalized Isatins: A Straightforward Access to Spiro‐Epoxyoxindoles. Issue 23 (May 2016) - Pace, Vittorio; Castoldi, Laura; Mamuye, Ashenafi Damtew; Langer, Thierry; Holzer, Wolfgang
Abstract: Chemoselective addition of in situ generated chloromethyllithium followed by ring‐closure of the intermediate alkoxide gives spiro‐epoxyindoles.